2012
DOI: 10.1590/s2179-83972012000400004
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da transferência inter-hospitalar nos resultados da intervenção coronária percutânea primária

Abstract: Background: Delays resulting from the transfer to perform primary percutaneous coronary intervention (PCI) have a negative impact on the benefits of the procedure. Methods: Prospective registry aimed at comparing the results of primary PCI in patients with ST-segment elevation myocardial infarction (STEMI) admitted or transferred to an interventional cath lab equipped hospital. Results: Between February 2009 and December 2011, 319 patients were included in the study with mean age of 59.8 ± 12 years, 28.5% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The mean ischemia time was 5.1 hours and the median door-to-balloon time was only 55 minutes, favored by the logistical conditions set forth in a previous publication. 10 Moreover, manual aspiration thrombectomy was used in 54% of the sample, and glycoprotein IIb/IIIa inhibitors and adenosine were administered prophylactically to 59% and 36% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The mean ischemia time was 5.1 hours and the median door-to-balloon time was only 55 minutes, favored by the logistical conditions set forth in a previous publication. 10 Moreover, manual aspiration thrombectomy was used in 54% of the sample, and glycoprotein IIb/IIIa inhibitors and adenosine were administered prophylactically to 59% and 36% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As a caveat to the prescription Glycoprotein IIb/IIIa receptor inhibitors, whose efficacy was demonstrated in studies performed before the routine use of dual antiplatelet therapy, showed a decline in their prescription, compared to previous publications. 13,14 The consolidation of oral dual antiplatelet therapy, the constant search for the balance between anti-ischemic efficacy and safety, as well as the advent of ADP inhibitors with higher power justify this finding, whereas the use of parenteral agents are restricted to specific and rescue situations, such as large thrombotic burden, coronary flow disorders, and thrombotic complications.…”
Section: Discussionmentioning
confidence: 99%